Electrophysiological activity of the pharyngoesophageal transition of total laryngectomees. (26th September 2016) - Takeshita‐Monaretti, Telma K.; Aguiar‐Ricz, Lílian; Bastos, Patrícia; Marques, Wilson; Ricz, Hilton
Abstract : Objectives/Hypothesis: To determine the association of the electrophysiological activity of the pharyngoesophageal transition with tracheoesophageal speech proficiency in total laryngectomees. Study Design: An observational (nonexperimental) study of the correlation type with a descriptive approach. Methods: Thirty‐four individuals (26 males), average age 62.5 years, total laryngectomees rehabilitated with the use of a tracheoesophageal prosthesis, were assessed for tracheoesophageal speech proficiency using an adapted protocol and classified as good, moderate, or poor speakers. Next they were submitted to electromyography of the muscles of the pharyngoesophageal transition with a needle electrode. The area to be examined was located by videofluoroscopy. Electromyographic analysis was characterized as normal, neurogenic injury (moderate to severe, severe, severe to total), myopathic injury, or inconclusive. The Fisher exact test was used to determine the association between the speech proficiency variables and electromyography. Results: in the final rating of tracheoesophageal speech proficiency, most laryngectomees were categorized as moderate (n = 24) and a few as good (n = 3). Electromyography revealed neurogenic injury in all laryngectomees, which was severe in most cases (n = 20), followed by severe to total (n = 10), and moderate to severe injury (n = 4). There was no significant association between he electromyographic analyses of neurogenic injuries and tracheoesophageal speech proficiency. Conclusions: Whether or not the musculature of the pharyngoesophageal transition of tracheoesophageal speakers had a preserved motor unit, did not prevent voice acquisition and was not associated with tracheoesophageal speech proficiency. However, further studies are needed in this area. Level of Evidence: 4. Laryngoscope, 127:1369–1375, 2017